Estabilidade do centro de força corporal e tempos máximos de fonação, pressão sonora e espectrografias vocais de sujeitos do sexo feminino - Frigo, Letícia Fernandez (2013)
Objectives: To investigate the relationship between muscle activation that makes up the body center of force (CF) and the vocal characteristics of adults females related to the maximum phonation time (MPT), the sound pressure (PS) and the spectrographic acoustic vocal characteristics. Methods: Cross-sectional observational analytical quantitative. Sample consisting of ten women of childbearing age (19-28 years old) without vocal complaints and without laryngeal disorders diagnosed by otolaryngologists. TMF collection / a /, the PS, evaluation of MEP and the transverse muscle activation, multifidus and pelvic floor. Vocal spectrography performed by Real Time Spectrogram (Kay Pentax ®) and analyzed by judges. Kappa and Spearman 5% tests were used. Results: Activation of transversus abdominis satisfactory in all subjects, no significant positive correlation between PS, TMF and the MEP values; most women with MPT / a / slightly below expectations and PS values within the expected activation and satisfactory multifidus, pelvic floor muscles and Oxford scale, with positive correlation, but not significant. Significant positive correlation between the MEP. and the definition of the second formant, a significant positive correlation between the measures and regular evaluation of perineal spectrographic trace. There was also a significant inverse correlation between activation of the multifidus and the width of the second formant. Conclusion: There was no significant correlation between the PS, TMF and MEP. values, activation of the multifidus, perineal muscles and Oxford scale, although most women showed satisfactory muscle activation while values were considered slightly below normal for TMF and normal PS. There was a correlation between measures of pelvic floor assessment and regularity spectrograplic trace, showing that the more activated the muscles, the smoother the trace and inverse correlation between the width of the F2 and the activation of the multifidus, showing a relationship between activation of the muscles that make up the CF and acoustic voice spectrographic.